E-Pain Reporter: A Digital Pain and Analgesic Diary for Home Hospice Care. Issue 2 (April 2017) - Mayahara, Masako; Wilbur, JoEllen; O'Mahony, Sean; Breitenstein, Susan
Informal hospice caregivers play a key role in managing patients' pain at home, but lack of adherence to doctor-prescribed analgesic regimens and medication errors are significant barriers to truly effective pain management. A digital pain diary may improve caregiver management of pain at home; however, most digital pain tools available today were developed without input from patients or caregivers. Accordingly, the purpose of this study was to develop a digital pain application (1) for hospice caregivers to record patient pain and analgesic use and (2) for nurses to monitor administration of analgesics by caregivers. Using advisory group methods, nurse case managers (n = 6), and informal caregivers (n = 3) helped us to convert a paper-based pain and analgesic diary into a digital format—the e-PAIN Reporter —and to refine the application. The e-PAIN Reporter provides information on patient pain assessment and pain management and reports to nurses in real time. Further testing is now needed to determine (1) the feasibility of using the e-PAIN Reporter and (2) its effectiveness in improving pain management for hospice patients.